MODEL KOOPERATIF STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS DI KELAS V SDN 008 SUMBER JAYA KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Muh. Nafsir (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low student social studies learning outcomes. The purpose of this study was toimprove student social studies learning outcomes through the application of STAD type cooperative learningmodels. This research is a classroom action research conducted at SDN 008 Sumber Jaya. The data used in thisstudy are data on teacher and student activities and social studies learning outcomes. This research wasconducted for two cycles and each cycle was carried out through four stages, namely planning, implementation,observation and reflection. The results showed the acquisition of teacher activity data in the first cycle of thefirst meeting with a percentage of 51%, the second meeting with a percentage of 64.5%, in the second cycle atthe third meeting the percentage of 76.5%, and at the meeting 4 percentages obtained were 86.5%. Whereasstudent activity on the percentage of the first cycle of the 1st meeting was 53%, the second meeting was 63.5%,in the second cycle the third meeting was 82%, and the fourth meeting was 91%. Learning outcomes in the initialdata obtained an average of 64.5, in daily tests I obtained an average class of 75, and in the second daily testobtained an average of 86.